The Numerical Simulation of the Atmosphere Delays Impact on Radar Measurement in Aviation - Kamil Krasuski; Artur Gos (Communications - Scientific letters of the University of Zilina, 2019)
The article presents numerical simulations with regard to determining the impact of the ionospheric and tropospheric delays on a radar-aircraft slant distance measurement. During the first experimental test, numerical calculations were made, showing the relationship between the ionosphere correction and the zenith angle in order to determine the measurement error of a radar-aircraft slant distance. During the second experimental test, numerical calculations were made demonstrating a relationship between the tropospheric correction and zenith angle in order to determine a measurement error of a radar-aircraft slant distance. The experimental test was conducted for the primary surveillance radar AVIA-W located on the grounds of the military aerodrome EPDE in Deblin. Based on the conducted research tests, it was found that the impact of the ionosphere delay can cause an error in a radar measurement above 4m. Moreover, influence of the troposphere delay can cause an error of a radar measurement by approximately 0.2m. The numerical simulation made in this research study may be used in the radiolocation of moving objects, as well as the GNSS satellite navigation in aviation.